IMPROVING STUDENT LEARNING OUTCOMES BY USING PROBLEM BASED LEARNING MODEL IN LEARNING THEMATIC CLASS III THEME OF GROWTH AND DEVELOPMENT OF LIVING CREATURES - Tantia; Nurmairina (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
This research aims to improve student learning outcomes by using the Problem Based Learning model in class III thematic learning with the theme "Growth & Development of Living Creatures". This research is Classroom Action Research (PTK) or classroom action research. This research was conducted at SDN 105330 Bangun Sari Tanjung Morawa. The subjects of this research were 32 class III students at SDN 105330 Bangun Sari. To collect data in this research, researchers used observation, provided test instruments and carried out documentation. The use of the Problem Based Learning model in thematic learning on the theme "Growth and Development of Living Creatures" in class III at SDN 105330 Bangun Sari Tanjung Morawa is carried out in 2 cycles. From the research results, it is known that in cycle I, of the 32 class III students at SDN 105330 Bangun Sari Medan, 10 students got an average score above the KKM. Meanwhile, 22 other students did not get a score above the KKM. In cycle II, of the 32 class III students, 15 students got an average score above the KKM and 17 other students still got a score below the KKM. In cycle III, out of 32 students, 25 students had scores above the KKM, only 7 students had scores below the KKM. The percentage of learning outcomes for class III students at SDN 105330 Bangun Sari at the time of observation was 25%. In cycle I, the percentage of learning outcomes for class III students increased to 43.75%. In cycle II the learning outcomes of class III students again increased to 53.12% and in cycle III there was a significant increase in the learning outcomes of class III students, namely to 93.75%. The Problem Based Learning model can improve the learning outcomes of class III students at SDN 105330 Bangun Sari in thematic learning with the theme "Growth & Development of Living Things".